FREE ENERGY ANALYSIS OF SOLVATED HER2 PROTEIN USING ALL-ATOM FORCE FIELD - Oktavia, Veni
Under normal circumstances, HER2 receptors help control how a breast cell grows, divides, and repairs itself. But in about 25% of breast cancers, overexpression of the HER2 protein can lead to the development of breast cancer itself. Inside the cell, the protein is solvated by water, therefore in this study, will be discussed about the dynamics of HER2 protein which is solvated in the water and also observe its free energy to find out the stability of protein when it is solvated. Thus we use molecular dynamics with all-atomic force field models. Using this all-atom method, we can find out the dynamics of proteins more specifically because this method measures the interaction of each atom which is simulated in the progam.